Effective Radiative Forcings Due To Anthropogenic Emission Changes Under Covid‐19 and Post‐Pandemic Recovery Scenarios. Issue 8 (20th April 2022) - Yu, Xiaochao; Zhang, Hua; Xie, Bing; Wang, Zhili; Zhao, Shuyun; Zhao, Defeng
Abstract: With the continuation of the Coronavirus Disease 2019 (Covid‐19) pandemic, the impacts of this catastrophe on anthropogenic emissions are no longer limited to its early stage. This study quantitatively estimates effective radiative forcings (ERFs) due to anthropogenic well‐mixed greenhouse gases (WMGHGs) and aerosols for the period 2020–2050 under the three latest Covid‐19 economic‐recovery scenarios using an aerosol‐climate model. The results indicate that reductions in both WMGHG and aerosol emissions under the Covid‐19 green recoveries lead to increases ranging from 0 to 0.3 W m −2 in global annual mean anthropogenic ERF over the period 2020–2050 relative to the Shared Socioeconomic Pathway 2‐4.5 scenario (the baseline case). These positive ERFs are mainly attributed to the rapid and dramatic decreases in atmospheric aerosol content that increase net shortwave radiative flux at the top of atmosphere via weakening the direct aerosol effect and low cloud cover. At the regional scale, reductions in aerosols contribute to positive ERFs throughout the Northern Hemisphere, while the decreased WMGHGs dominate negative ERFs over the areas away from aerosol pollution, such as the Southern Hemisphere oceans. This drives a strong interhemispheric contrast of ERFs. In contrast, the increased anthropogenic emissions under the fossil‐fueled recovery scenario lead to an increase of 0.3 W m −2 in global annual mean ERF in 2050 compared with the baseline case, primarily due to the contribution of WMGHG ERFs. The regional ERF changes are highly dependent on local cloud radiative effects. Plain Language Summary: As a result of the Covid‐19 pandemic, the unprecedented containment has imposed on energy demand and other structural changes in transport globally. These changes may further affect future emission levels, thus inducing climate changes at the global and regional scales. In this study, we estimated effective radiative forcings (ERFs) due to anthropogenic forcing agents, such as well‐mixed greenhouse gases (WMGHGs), and aerosols, under the three latest Covid‐19 economic recovery scenarios (fossil‐fueled, moderate green, and strong green recoveries). Despite large decreases in both WMGHG and aerosol emissions under two green recovery scenarios, we found the aerosol ERF that mainly occurs over the Northern Hemisphere is the dominant contributor to the total positive ERFs over the period 2020–2050. Conversely, the ERFs over the Southern Hemisphere oceans turn negative due to the reduction in WMGHG emissions, which partly offset the effects of the abovementioned changes in aerosols, and result in asymmetric interhemispheric patterns in Earth's radiation budget in future. Key Points: Reductions in aerosol emissions under two green recoveries dominate the increases in total effective radiative forcing (ERF) from 2020 to 2050 Compared to 2020, the total ERF increases in 2050 due to increased greenhouse gas under a fossil‐fueled recovery Interhemispheric contrasts of ERF are striking due to the simultaneous decreased anthropogenic forcing agents